Longevity Through Panchakarma in Healthy Life - Mangal, Gopesh; Nanarkar, Prasad; Garg, Gunjan (International Research Journal of Ayurveda & Yoga, 2022)
In age of competition and industrialization risk of lifestyle disorders is increased. Lifestyle disorders are causing a greater number of mortality and morbidity. Lifestyle disorders is not only limited to adult but also it is found in young age. In previous few studies result shows that over 61 per cent of all deaths in India attributed to lifestyle or non-communicable diseases. They are spread in both urban and rural areas. This disease is burden over society as well as allopathy medicine, because they only control the disease not totally cure. On other side principle of ayurveda first deals with preventive care of healthy individuals and curative care of diseased individuals. Ayurveda is worked at four levels first is Nidanparivarjana (avoid causative factors), Sanshodhana (detoxification), Samshamana (palliative medicine) and Pathyapathya (specific diet according to disease). In this Sanshodhana is mainly concerned with Panchakarma. Panchakarma is use as preventive as well as curative purpose. Panchakarma includes Vamana (therapeutic emesis), Virechana (therapeutic purgation), Niruha Basti (therapeutic decoction enema), Anuvasan Basti (therapeutic unctuous enema) and Nasya (medication through nasal route). Various Samhita describe Dinacharya (daily regimen) and Rutucharya (seasonal regimens) in which Acharya explained about daily and seasonal Panchakarma procedure for healthy life. So, this article aims to review the role of different type Panchakarma in order to explore the scientific approach for welfare of human beings.